1992
DOI: 10.1007/bf02283116
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rheumatoid arthritis with anti CD4 monoclonal antibody. Open study of 25 patients with the B-F5 clone

Abstract: Twenty-five defined severe RA patients (pts) (17 F, 8 M) were treated in an open study with a CD4 murine monoclonal antibody (Mab) (B-F5 clone, IgG1). Mab's daily dose was 10 mg (1 pt), 15 mg (2 pts), 20 mg (17 pts), 30 mg (4 pts) and 50 mg (1 pt) for 10 days. Tolerance was fair. Clinical improvement occurred during treatment period or within the first month in all but 2 patients, irrespective of Mab dosage. Improvement duration was variable (1 to 12 months), half of the patients still show signs of improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 16 publications
(9 reference statements)
0
18
0
Order By: Relevance
“…Recently, it was reported that in vivo blockade of either TNF-␣ or IL-6 signals by the administration of anti-TNF-␣ monoclonal antibody, anti-IL-6 monoclonal antibody, or anti-IL-6R antibody to RA patients was clinically very effective (53)(54)(55). The clinical efficacy of these blocking antibodies strongly indicates that correction of the dysregulation in cytokine production may be a rational approach for the treatment of RA, although the pathogenesis of RA still remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that in vivo blockade of either TNF-␣ or IL-6 signals by the administration of anti-TNF-␣ monoclonal antibody, anti-IL-6 monoclonal antibody, or anti-IL-6R antibody to RA patients was clinically very effective (53)(54)(55). The clinical efficacy of these blocking antibodies strongly indicates that correction of the dysregulation in cytokine production may be a rational approach for the treatment of RA, although the pathogenesis of RA still remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 MAb have been used for the treatment of advanced RA in a limited number of patients. All of the published uncontrolled phase I and phase I1 studies using multiple dosage regimens of CD4 MAb in RA have shown a direct amelioration of arthritis activity lasting for several months (5)(6)(7)(8)(9)(10)(11)(12). Three of these studies involved the cM-T412 CD4 MAb (10)(11)(12).…”
Section: Van Der Lubbe Et Almentioning
confidence: 99%
“…the treatment of autoimmune diseases in experimental animal models (3,4), open-label studies were performed in patients with RA (5)(6)(7)(8)(9)(10)(11)(12). CD4 MAb treatment was well tolerated and induced a rapid amelioration of arthritis activity in the majority of the patients studied.…”
mentioning
confidence: 99%
“…In addition, recent progress in the field of cytokine research has led to the idea that these proinflammatory cytokines might be optimal therapeutic targets for RA. In fact, recent clinical trials of anticytokine therapy for RA (5)(6)(7)(8)(9) encouraged this idea. However, the roles of the individual cytokines for the pathology of RA have not been fully dissected and understood.…”
mentioning
confidence: 99%